2021
DOI: 10.3390/diagnostics11112047
|View full text |Cite
|
Sign up to set email alerts
|

A Step Closer to the “Fourth 90”: A Practical Narrative Review of Diagnosis and Management of Nutritional Issues of People Living with HIV

Abstract: The quality of life of people living with HIV (PLWH) has remarkably increased thanks to the introduction of combined antiretroviral therapy. Still, PLWH are exposed to an increased risk of cardiovascular diseases, diabetes, chronic kidney disease, and liver disease. Hence, the purpose of this review is to summarize the current knowledge about diagnosis and nutritional management with specific indication of macro and micronutrients intake for the main comorbidities of PLWH. In fact, a prompt diagnosis and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 158 publications
0
9
0
Order By: Relevance
“…In an ageing population of PWH that is largely on ART and treated for hepatitis B and C viral infections, NAFLD has emerged as the most common cause of liver disease. [6][7][8][17][18][19][20][21][22][23][24][25] In prior studies of persons with HIV mono-infection, NAFLD prevalence was reported in the range of 15%-59%. 7,9,[26][27][28][29][30] Clearly, case/phenotype definitions and alcohol use thresholds dictate the frequencies of each SLD category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an ageing population of PWH that is largely on ART and treated for hepatitis B and C viral infections, NAFLD has emerged as the most common cause of liver disease. [6][7][8][17][18][19][20][21][22][23][24][25] In prior studies of persons with HIV mono-infection, NAFLD prevalence was reported in the range of 15%-59%. 7,9,[26][27][28][29][30] Clearly, case/phenotype definitions and alcohol use thresholds dictate the frequencies of each SLD category.…”
Section: Discussionmentioning
confidence: 99%
“…In an ageing population of PWH that is largely on ART and treated for hepatitis B and C viral infections, NAFLD has emerged as the most common cause of liver disease 6–8,17–25 . In prior studies of persons with HIV mono‐infection, NAFLD prevalence was reported in the range of 15%–59% 7,9,26–30 .…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The attainment of such ambitious treatment goals requires robust combination ART such as bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF). 4 The INSTI-based single-tablet regimen (STR), Biktarvy ® (BIC/FTC/TAF), can meet the high demands of a contemporary ART. 5 BIC/ FTC/TAF is taken once daily, with or without food, 6 and is indicated 1 in Switzerland for the treatment of HIV type 1 (HIV-1) infection in treatmentnaive adults or as a replacement for the current antiretroviral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Substantiating the benefits of physical activity and a healthy diet as self-care to reduce the risk of Type 2 Diabetes, Duncan et al ( 2020 ) conducted a 6-month intervention with older PLWH in the United Kingdom (UK) and found that physical activity and adhering to a healthy diet resulted in weight reduction by 7% and a lowered Homeostatic Model Assessment for Insulin Resistance (HOMA -IR) score of older PLWH. Similarly, Bavaro et al ( 2021 ) assert that self-care practices to reduce weight through diet control and physical activity achieve glycaemic control.…”
Section: Introductionmentioning
confidence: 99%